On the Effects of Personalizing Vibrotactile Feedback to Facilitate User Interaction With a Robotic System - Sudip Hazra; Panos S. Shiakolas (IEEE Access)
Distinguishable vibrotactile feedback can convey information non-verbally and complete the sensory loop when using assistive devices. Feedback can increase acceptance of assistive devices but could require personalization as these devices need to adapt to user capabilities and preferences that may affect the location for inducing feedback. Developing personalized feedback for each user may be ideal, but impractical if demand for these devices increases. In this research, we evaluate the hypothesis that the ability to define, generate, and use personalized feedback is preferred and should be provided. The hypothesis is evaluated using a system capable of capturing and recognizing non-verbal inputs, providing vibrotactile feedback to verify the identified action, and executing the verified action. Evaluation focuses on determining the ability to initiate actions using the system architecture, and define, generate, and use personalized feedback. In addition to recording performance metrics (success or failure), the participants also completed the NASA TLX and post-evaluation questionnaires. Based on results, the actions can be initiated using the system architecture, and defining, generating, and using personalized feedback was found to be preferable with the success rate reaching 100% after only three successive repetitions, and could decrease mental demand and effort while interacting with the system.